The Transformation of the Social Imaginary on Women’s Sexuality in Indonesian Literature from the New Order to Reformasi Eras - Udasmoro, Wening; Saktiningrum, Nur (2022)
In this research, we explored the social imaginary that relates to women’s sexuality based on the writings of several prominent Indonesian female authors. We argue that the social imaginary is not only a social construction but also a construct created through an individual’s active participation. Historically, the social imaginary in Indonesia has been tied to nationalism; however, it has gradually shifted toward the individual perspective. In particular, this study examined the construction of the social imaginary in Indonesia by comparing and differentiating literary works created under two political regimes: the authoritarian New Order regime (1968–1998) and the more democratic Reformasi regime (1999–present), wherein individuals—especially women—were given more space and liberty to participate in the construction of the social imaginary of their sexuality. This study focused primarily on two important research questions. First, how has the social imaginary of women's sexuality, as contested by Indonesian women authors in their literary works, changed from the New Order era to the Reformasi era? And second, how has the re-emergence of religious, political, and social powers during the Reformasi era contributed to authors’ contestations of women’s sexuality? The content analysis of selected literary works revealed that the social imaginary of women’s sexuality changed alongside the changes in Indonesia’s political regimes. During the New Order era, the social imaginary was controlled by the hegemonic power of the State. In the early period of Suharto’s rule, women authors were co-opted by the State’s power, whereas its later years were marked by the struggles of women authors against his authoritarian government. The Reformasi era gave way for liberty in women’s discussions of their sexuality, but this freedom was found to be temporary, its ephemerality compounded by new, religiously oriented conservative powers’ attempts to push back against the new wave of self-expressive women authors and restore women’s position to one of suppression and subordination. © 2022. Journal of International Women''s Studies. All Rights Reserved.